Approaching Inpatient Glycemic Control Using Six Sigma Methodology - Khthir, MD, CPHQ, CCD, Rodhan (International Journal of Innovative Research in Medical Science, 2021)
Process variation affects almost all healthcare processes. Wide fluctuation of blood glucose values is very common in hospitalized patients and may impact the outcome of care in negative way. The purpose of this article is to illustrate how to study the process variation using Six Sigma approach and how to us it teaching healthcare quality.